Increasing nutrient inputs over the last 500 years in an Italian low-impacted seagrass meadow. (January 2022) - Casella, Nicolò; Careddu, Giulio; Calizza, Edoardo; Sporta Caputi, Simona; Rossi, Loreto; Belluscio, Andrea; Ardizzone, Giandomenico; Calcagnile, Lucio; Quarta, Gianluca; D'Elia, Marisa; Costantini, Maria Letizia
Abstract: Posidonia oceanica is a seagrass endemic to the Mediterranean and it has been widely used as a bioindicator. We studied the layers of a 500-year-old matte using a multiproxy approach (δ 13 C, δ 15 N, 14 C and C and N concentrations in seagrass debris) in order to evaluate the potential of P. oceanica as a long-term environmental indicator of N pollution and CO2 emissions. From 1581 to 1800, accumulation rate was ca. 0.35 cm year −1, while in the last 100 years it has amounted to ca. 0.51 cm year −1 . We observed increasing δ 15 N values with height in the vertical matte profile, indicating an increase in anthropogenic organic N inputs over time. In contrast, no clear trend in the δ 13 C values was observed. This study reconstructs the long-term impact of human activities on a seagrass meadow located off the Italian coast, yielding long-term background information that can help managers to implement efficient plans. Highlights: 14 C dating of the matte revealed a chronological record dating back ca. 500 years. Matte accretion rate was 0.35 cm year −1 (0.51 cm year −1 in the last 100 years). P. oceanica δ 15 N increase over time, from ca. 0‰ to ca. 3‰ in the recent layers. The highest δ 15 N in the recent layers is indicative of anthropogenic N inputs. No clear temporal trend in the δ 13 C values of P. oceanica was observed.